2019
DOI: 10.4103/ijd.ijd_149_18
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of primary cutaneous amyloidosis in a tertiary care center of Eastern India reveals insignificant association with friction, scrubbing, and photo-exposure: How valid is the “keratinocyte hypothesis”?

Abstract: Introduction:Primary cutaneous amyloidosis (PCA) can be classified into four principal categories: macular amyloidosis, lichen amyloidosis, biphasic, and nodular amyloidosis. Some unusual variants such as widespread diffuse hyperpigmentation without papules, poikiloderma like involvement, lesions following Blaschko's line, etc., have also been reported. However, not much data are available regarding the demography, epidemiology, clinical patterns, and distribution and histopathological findings, especially fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…The aim of this monocentric retrospective study was to analyze primary localized cutaneous amyloidosis in the Central European region concerning demographic data, body distribution, comorbidities, treatment practices and treatment outcomes. While PLCA is more prevalent in Asian and South American populations, epidemiologic data regarding PLCA in the Caucasian population are limited [2,3,[55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this monocentric retrospective study was to analyze primary localized cutaneous amyloidosis in the Central European region concerning demographic data, body distribution, comorbidities, treatment practices and treatment outcomes. While PLCA is more prevalent in Asian and South American populations, epidemiologic data regarding PLCA in the Caucasian population are limited [2,3,[55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of PCA remains unclear although genetic predisposition, approximately 10% of patients have a family history of PCA 3 . Racial factors, gender, atopy, sun exposure, and frictional epidermal damage are also thought to contribute to the etiopathogenesis 4 . Studies have shown that the occurrence, development, and aggravation of many skin diseases are closely related to the destruction of skin barrier structure 5 .…”
Section: Introductionmentioning
confidence: 99%
“…3 Racial factors, gender, atopy, sun exposure, and frictional epidermal damage are also thought to contribute to the etiopathogenesis. 4 Studies have shown that the occurrence, development, and aggravation of many skin diseases are closely related to the destruction of skin barrier structure. 5 Once any tissue or chemical composition in the skin barrier is abnormal, it will trigger the etiology and pathological process of clinical skin diseases.…”
mentioning
confidence: 99%
“…4 Factors such as race, gender, atopy, sun exposure, and the debated frictional epidermal damage have also been proposed as contributors to its etiopathogenesis. 5 Treating PCA remains a formidable challenge for clinicians due to the absence of evidence-based treatment guidelines. Many treatment avenues have been explored, spanning retinoids, corticosteroids, cyclophosphamide, laser treatment, and phototherapy, etc.…”
Section: Introductionmentioning
confidence: 99%